Approaches to identify genetic variants that influence the risk for onset of fragile X-associated primary ovarian insufficiency (FXPOI): a preliminary study - Allen, Emily G.; Grus, Wendy E.; Narayan, Sarayu; Espinel, Whitney; Sherman, Stephanie L. (Frontiers in Genetics, 2014)
Fragile X-associated primary ovarian insufficiency (FXPOI) is due to an X-linked mutation that results from the expansion of a CGG repeat sequence located in the 5′ untranslated region of the FMR1 gene (premutation, PM). About 20% of women who carry the PM have cessation of menses before age 40, a clinical condition known as premature ovarian failure (POF). This leads to a 20-fold increased risk over women in the general population. Thus, this single gene mutation has a major effect on reducing a woman's reproductive life span. Based on survival analysis of about 1300 women, we showed that the mean age at menopause among PM carriers is reduced compared with noncarriers, even after removing women who reported POF. This suggests that the majority of women with the PM, not just a subset, experience ovarian insufficiency earlier than noncarriers. To better understand the underlying mechanism of the PM and to identify genes that modify the variable expressivity of FXPOI, we conducted two pilot studies. The first focused on five common variants known to reduce age at menopause. We genotyped these SNPs in 72 women with a PM who experienced menopause and found a significant association with the total SNP risk burden and age at menopause. This suggests that these SNPs influence onset of FXPOI, after adjusting for the effect of the PM allele. In the second approach, we conducted whole genome sequencing on 10 PM carriers, five with onset of FXPOI prior to age 30 and five who experienced menopause after age 47 years. Although only a pilot study, we describe our preliminary approach to identify potential variants that may play a role in modifying onset of FXPOI and potentially play a role in idiopathic primary ovarian insufficiency. The overarching goal of both approaches is to identify predictor variants that may identify women predisposed to early onset FXPOI and to further identify genes involved in defining a woman's reproductive life span.